Shale Heterogeneity in Western Hunan and Hubei: A Case Study from the Lower Silurian Longmaxi Formation in Well Laidi 1 in the Laifeng-Xianfeng Block, Hubei Province - Peng Zhang; Junwei Yang; Yuqi Huang; Jinchuan Zhang; Xuan Tang; Chengwei Liu (Geofluids)
Shale heterogeneity directly determines the alteration ability and gas content of shale reservoirs, and its study is a core research topic in shale gas exploitation and development. In this study, the shale from the Longmaxi Formation from well Ld1 located in western Hunan and Hubei is investigated. The shale’s heterogeneity is analyzed based on shale mineral rocks, microslices, geochemistry, and low-temperature N2 adsorption-desorption. It is found that the shales of the Longmaxi Formation from well Ld1 are mainly composed of siliceous shale, mixed shale, and clayey shale. The three types of shale facies exhibit strong heterogeneity in terms of the occurrence state of organic matter, organic content, mineral composition, microstructure and structure, brittleness, and micropore type. Sedimentation, late diagenesis, and terrigenous input are the main factors influencing the shale’s heterogeneity. With a total organic carbon (TOC) of 0.41%-4.18% and an organic matter maturity (Ro) of 3.09%-3.42%, the shales of the Longmaxi Formation from well Ld1 are in an overmature stage, and their mineral composition is mainly quartz (5%-66%) and clay minerals (17.8%-73.8%). The main pore types are intergranular pores, intragranular pores, microfractures, and organic pores. The results of the low-temperature N2 adsorption-desorption experiment show that the shale pores are mainly composed of micropores and mesopores with narrow throats and complex structures, and their main morphology is of a thin-necked and wide-body ink-bottle pore. Based on the Frenkel-Halsey-Hill (FHH) model, the pore fractal dimension is studied to obtain the fractal dimension D1 (2.73-2.76, mean 2.74) under low relative pressure (P/P0≤0.5) and D2 (2.80-2.89, mean 2.85) under high relative pressure (P/P0>0.5). The shales of the Longmaxi Formation in the study area have a strong adsorption and gas storage capacity; however, the pore structure is complex and the connectivity is poor, which, in turn, imposes high requirements on reservoir reformation measures during exploitation. Moreover, the fractal dimension has a positive correlation with organic matter abundance, TOC, clay mineral content, and pyrite content and a negative correlation with quartz content. Since the organic matter contained in the shales of the Longmaxi Formation in the study area is in the overmature stage, the adsorption capacity of the shales is reduced, and the controlling effect of organic matter abundance on the same is not apparent.